Does Concessionary Aid Lead to Higher Investment Rates in Low-Income Countries? - Levy, Victor (The Review of Economics and Statistics, 1987)
Goedde, Alan G., U.S. Multinational Manufacturing Firms: Determinants and Effects of Foreign Investment, Ph.D. dissertation, Duke University (1978). Grubaugh, Stephen G., The Process of Direct Foreign Investment, working paper, Bentley College, Aug. 1986. Helpman, Elhanan, Simple Theory of International Trade with Multinational Corporations, Journal of Political Economy 3 (June 1984), 451-471. Horst, Thomas, Firm and Industry Determinants of the Decision to Invest Abroad: An Empirical Study, this REVIEW 54 (Aug. 1972), 258-266. ____,_ At Home Abroad: A Study of Domestic and Foreign Operations of the A merican Food-Processing Industry (Cambridge, MA: Ballinger, 1974). Hymer, Stephen H., The International Operations of National Firms: A Study of Direct Foreign Investment, Ph.D. dissertation, M.I.T. (published by M.I.T. Press, 1976). Judge, George G., R. Carter Hill, William E. Griffiths, Helmut Lutkepohl, and Tsoung-Chao Lee, Introduction to the Theory and Practice of Econometrics (New York: John Wiley and Sons, 1982). Macdougal, G. D. A., The Benefits and Costs of Private Investment from Abroad: A Theoretical Approach, Economic Record 36 (Mar. 1960), 13-35. Markusen, James R., Multinationals, Multiplant Economies, and the Gains from Trade, Journal of International Economics 3/4 (May 1984), 205-226. Pindyck, Robert S., and Daniel L. Rubinfeld, Econometric Models and Economic Forecasts, second edition (New York: McGraw-Hill, 1981). Rugman, Allen M., Inside the Multinationals: Economics of Internal Markets (New York: Columbia University Press, 1981). Vaupel, James W., and Joan P. Curhan, Making of Multinational Enterprise (Cambridge: Division of Research, Graduate School of Business Administration, Harvard University, 1969).